Encyclopedia of Foods and Their Healing Power - George D. Pamplona-Roger (Madrid, Spain : Editorial Safeliz S L, 2010)
Wholosome foods, harmful foods A broad and up-to-date encyclopaedia, in which the latest research on the science of foods, nutrition and dietetics is presented. It presents 150 diseases, with an indications of the foods whose amount must be increased or reduced in each case. You will learn the advantages and disadvantages of all types of foods. You will be able to prevent and cure most of them, thanks to the 700 monographic food-by-food data boxes encompassing the whole world. Over 300 diets with suggestions of what should be had for breakfast, lunch and dinner. The book aims to provide us with sufficient understanding of food products to enable us to make effective decisions relative to our health.
v. 1. Encyclopedia of foods and their healing power : a guide to food science and diet therapy --
&#x000A
v. 2. Encyclopedia of foods and their healing power : a guide to food science and diet therapy --
&#x000A
v. 3. Encyclopedia of foods : healthy recipes
Includes bibliographical references and index
uaj 23/06/2014
Ref
Keywords: Food. Diet; Health; Health and Life